2019
DOI: 10.18488/journal.1006.2019.91.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Earnings Management Practices among Listed Firms: A Study on Post Stock Market Crisis Period in Bangladesh

Abstract: This paper investigates the effect of corporate governance on earnings management practice of listed firms in Bangladesh during post stock market crisis period. The data set consists of 300 firm year observation from 2011-15. We have used six (6) corporate governance variables as independent variables namely board Size, CEO duality, board independence, board meeting, audit committee independence and ownership concentration. Leverage and firm size have been used as control variables. Our dependent variable is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Based on the idea that the higher the proportion of independent commissioners in the firm, it is expected that the empowerment of the board of commissioners can carry out supervisory duties and provide advice to the board of directors effectively and added value to the firm (Perdana & Raharja, 2014). However, some study results show the existence of the independent commissioner in firm rated not yet effective enough for monitoring the management firm that why market participants have not fully believed the performance of independent commissioners in the firm, specifically if the influence of family ownership (Kusumaningtyas & Andayani, 2015;Muktadir-Al-Mukit & Keyamoni, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the idea that the higher the proportion of independent commissioners in the firm, it is expected that the empowerment of the board of commissioners can carry out supervisory duties and provide advice to the board of directors effectively and added value to the firm (Perdana & Raharja, 2014). However, some study results show the existence of the independent commissioner in firm rated not yet effective enough for monitoring the management firm that why market participants have not fully believed the performance of independent commissioners in the firm, specifically if the influence of family ownership (Kusumaningtyas & Andayani, 2015;Muktadir-Al-Mukit & Keyamoni, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that by holding a larger ownership, management can ensure greater participation in corporate affairs and ensure corporate governance implementation and sustainability. Nevertheless, in most cases, they hold the shares to maintain and take advantage of ownership rather than adding value to the firm (Muktadir-Al-Mukit & Keyamoni, 2019;Connelly et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, regardless of positive or negative earnings, companies, through earnings management, maintain accounting numbers consistently by either accumulating or removing funds from reserve accounts (Potharla & Dissanayake 2022). Muktadir et al (2019) argue that earnings management involves the use of managerial discretion in the application of accounting methods or the manipulation of transactions through accounting practices that impact the distribution of wealth among the firm, investors, managers, and society. Adamczyk and Franek (2022) define earnings management as the managerial act of increasing or decreasing the current accounting income of a firm without altering long-term profits.…”
Section: Corporate Governance and Earning Managementmentioning
confidence: 99%
“…Although it is clear from the literature that private property and the judicial framework are essential for a fully operational financial sector, some scholars have indicated that the critical function of national governance or institutional arrangements in adjusting policies for capital markets and their advancement should not be disregarded (Agyemang et al, 2018;Antonio et al, 2019;Muktadir-Al-Mukit & Keyamoni, 2019;Cormier et al, 2019;Samanta & Johnson, 2020;Appiah-Kubi et al, 2020a). The claim is that countries with weak financial markets, which may make it extremely difficult for rivals to access financing, are typically those with weak governance or institutional structures, which include control of corruption, government effectiveness, political stability, regulatory quality, and the rule of Law and voice and accountability.…”
Section: Literature Reviewmentioning
confidence: 99%